NETWORK AND E-COMMERCE NET GENERATION: VLOGGING - Rahmawati Zulfiningrum; Amida Yusriana (Avant Garde, 2018)
E-commerce transactions by utilizing a variety of marketplace platform through the Internet media increasingly in demand by the people in Indonesia. Vlogs are social networks hosted by Net Gener where they can share information, expand communication networks and establish an N-fluence network. Vlog as the development of the blog with its audio-visual capabilities make the voice of the consumer becomes more expressive. Vlogging is much more N-fluencial because the information reviews from a vlogger are much more appealing to Followers and viewers than reviews of unknown experts. This research discusses the development of vlog and its utilization for e-commerce (virtual market) through communications network in Net Gener era, along with the increasing of vlogging trend where consumer purchase decision is quickly influenced by N-fluence network through social media. The result is that vlogging networks can be an important option for e-commerce producers to promote products and build relationships with their consumers, the Net-Gener.for e-commerce companies who were capable of viewing opportunities, vlog is the latest innovations.